The essential writings of Sudhir Kakar - Kakar, Sudhir (New Delhi ; New York : Oxford University Press, 2001)
"With an introduction by T.G. Vaidyanathan, this Sudhir Kakar reader contains extracts from several of his books, which have been translated into all the major languages. Included are psychoanalytical reflections on dominant themes in the emotional life of Hindu men, psychobiographical essays on such cultural heroes as Ramakrishna, Vivekananda and Gandhi, the unveiling of the erotic secret in the Radha and Krishna legend, the healing secret of the guru, love in Hindi cinema, and the psychology of religious fanaticism." "This book, which focuses for the first time on a living writer, as part of the Essential Writings series, is indispensable for a psychological understanding of the country as it establishes itself in this millennium. It is meant for students of psychology, South Asian culture and sociology, as well as the general reader."--BOOK JACKET.
Introduction by / T. G. Vaidyanathan -- I. Childhood and Identity -- 1. Mother and Infants -- 2. The Child in Indian Tradition -- 3. The Revolutionary Yogi: Childhood of Swami Vivekananda -- II. Culture and Healing -- 4. Lord of the Spirit World -- 5. The Guru as Healer -- 6. The Body Image -- 7. Clinical Work and Cultural Imagination -- 8. The Maternal-Feminine in Indian Psychoanalysis -- III. Erotic Love -- 9. The Cloistered Passion of Radha and Krishna -- 10. Gandhi and Women -- 11. Lovers in the Dark -- IV. Religion and Psyche -- 12. Ramakrishna and the Mystical Experience -- 13. The Virtuous Virago -- 14. Meeting the Mullahs -- 15. Religious Conflict in the Modern World.
Includes bibliographical references (p. [382]-386) and index.
Keywords: Psychoanalysis and culture -- India